The Effectiveness Of Sharia Micro-Enterprise Capital Financing On The Development Of Msmes In Indonesia - Faizi Faizi; Sulthan Suci Yudhistira Sulthan Suci Yudhistira (ITB AAS INDONESIA Surakarta, 2023)
The existence of micro, small, and medium-sized enterprises (MSMEs) is an important factor in society’s progress. It also plays an important role in Indonesia’s economic recovery process. MSMEs play an important role in the Indonesian economy because of the large number of industries in each economic sector. The purpose of this study is to analyze and determine the effectiveness of business capital financing on MSMEs development in BMT Bina Ummat Sejahtera (BUS) Pondok Gede. Testing the effectiveness of Islamic financial institution financing is important for measuring the extent to which disbursed financing is effective. The research method used was descriptive qualitative, using a case study approach. Data collection techniques included observation, interviews, and documentation to managers and members/customers BMT Bina Ummat Sejahtera (BUS) Pondok Gede. The results of this study show that the business capital financing scheme was implemented by Fatwa DSN-MUI No.07/DSN-MUI/IV/2000 on Mudharabah financing. The effectiveness of business capital financing distribution is measured using five main indicators: accuracy of targets, achievement of goals, program socialization, program monitoring, and financing procedures that have been running effectively and have a positive impact on the development of MSMEs assisted by BMT Bina Ummat Sejahtera (BUS) Pondok Gede.